Epidermal nevus of the breast and arm with hypertrophic lesions in the armpit. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
The epidermal nevus is due to a post-zygotic mutation affecting a primordial keratinocyte during the fetal life (2). From the mutated keratinocyte originates a cell clone that runs along the lines of Blaschko. In the more extensive cases the mutation can also affect a gonadal cells and the consequent gonadal mosaicism may give rise to a generalized disease in the offspring, for example congenital ichthyosis bullosa (1). Our case is characterized by a marked warty appearance on the axillary region. The particular environmental conditions of the folds can explain the greater evidence in this site of some lesions characterized by epidermal hyperplasia as seborrheic warts, pemphigus vegetans, acanthosis nigricans, granular parakeratosis and, in this case, epidermal nevus.